THE IMAGE OF WOMAN IN THE CONTEXT OF MYTHS: LILITH AND PANDORA - Sema ÖCAL ÇAĞLAYAN (International Journal of Eurasia Social Sciences, 2023)
The issue of women in the context of gender and myths has been revived due to the feminist movements of the late 20th century. Feminists, who mostly ignored the unpleasant features of female characters in myths, focused instead on their independence and desire for autonomy. Within the scope of the research, the effect of the female image in the myths on the construction of gender is revealed with examples of works of art, rather than readings on theology, mythology or historiography. Myths are implicit realities that enrich and develop over time. Within the scope of the research, the positioning of women in history, making them a chosen or unselected figure, making them sacred or passive, and the way they are the source of myths are discussed over two myths: Lilith and Pandora. In this sense, the myths of Lilith and Pandora have been tried to be revealed as 'living myths' rather than in terms of 'fiction' and the ways in which the male-dominated system is constructed over myths. Here, it is mentioned about the sociological context of myths, the conscious creation of social rules and the creation of a foundation worth living. This study is the product of a qualitative research and focuses on the subject of gender and related artworks through the myths of Lilith and Pandora. It aimed to obtain a new perspective by establishing the gender relationship with the Pandora myth and Lilith's anti-authoritarian attitude. How gender roles are structured by the system is discussed through metaphorical elements and myths. The main reason for choosing the examples of Lilith and Pandora is that they are the starting point in the context of women in myths, apart from presenting a comparative research. Rejecting her secondary position, Lilith escaped, embraced her inner evil, and turned into a demon. Like Pandora, Lilith could not resist the temptation of disobedience. According to one myth, a box is opened; in another, authority is challenged. The result of both is the end of heaven and the beginning of evil.